Pengaruh Digital Leadership terhadap Kinerja Perusahaan Startup di Jawa Timur - Vincensius Purnomo; Stanly Tejasukmana; Juniarti Juniarti (Business Accounting Review, 2021)
Firm performance is one of the most commonly found instruments in determiningmanagement decisions to manage the company. Firm performance can be divided into two perspectivesto determine financial performance and non-financial performance. Various studies have beenconducted to determine the effect of digital leadership on financial performance, and these studieshave influential results. Several previous studies have also found that digital leadership has aninfluence on non-financial performance, and these studies have mixed results. This study aims to examine the application of digital leadership applied to startup companies in EastJava which is a determining factor for the creation of a competitive advantage that can have an impacton financial performance and non-financial performance.In this study, a questionnaire-based survey was conducted to collect data on startup companiesin East Java. This study uses non-probability sampling where not all members of the population havethe same opportunity to be selected because they do not meet several criteria. Specifically, thisresearch uses purposive sampling technique, namely the sampling technique by setting several samplecriteria and selecting samples that meet the predetermined criteria. Then it will be analyzed usingWarpPLS 8.0 Software.